Clinical students’ reflections on the preclinical anatomy learning experience - Syarifah A. Syed Abd Halim; Muhamad Saiful Yusof; Mohamad N. Yaman; Shazrina Ahmad Razali; Tg Fatimah M. Tengku Muda; Ramiza Ramza Ramli; Fairrul Kadir; Siti N.H. Hadie (Elsevier B.V., 2022)
Objectives: Anatomy is a fundamental pillar of medical knowledge that bridges basic medical science knowledge and clinical practice. However, integrated modern medical curricula have reduced the anatomy teaching content, and cadaveric dissection is no longer conducted. Medical graduates who lack anatomy knowledge are anticipated to be inadequately equipped for safe clinical practice. This study was aimed at exploring clinical year students’ experiences regarding their anatomy learning during the preclinical phase in Malaysian medical schools. The findings reflect how the students’ preclinical anatomy training prepared them for their clinical years of study. Methods: A qualitative phenomenology study using the focus group discussion method was conducted on 30 final-year students from four public universities. Four focus group discussion sessions were conducted, and students’ responses were transcribed and converted to electronic formats. The transcripts were analyzed thematically with ATLAS.ti software. Results: The first-cycle coding of the text analysis generated 157 open codes based on the phrases used by the participants. The subsequent coding cycle produced 16 axial codes groups of open codes with similar features. During the final coding cycle, the content and interrelations between the axial codes were categorized into six codes: (1) preclinical anatomy learning experience, (2) anatomy content and teaching, (3) anatomy-related competency, (4) the importance of anatomy knowledge in clinical practice, (5) the importance of early exposure to applied clinical anatomy, and (6) suggestions for future anatomy education. Conclusions: The six identified themes reflected students’ perceptions of their anatomy learning experience, the challenges that they faced during their preclinical years, and their opinions regarding the anatomy knowledge and skills that are functionally relevant during the clinical years. Their responses also echoed the need to improve anatomy teaching and learning, thereby emphasizing the importance of early clinical integration and application